Fiber-reinforced resin and integrally molded product

CN116438069BActive Publication Date: 2026-10-27TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180075946.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-18
Filing Date
2021-10-27
Publication Date
2026-10-27
Estimated Expiration
2041-10-27

AI Technical Summary

Benefits of technology

[0014]通过使用本发明的纤维增强树脂,在热塑性树脂区域与其他部件的熔接时不易发生损伤,能够制作具有优异的拉伸剪切接合强度的一体化成型品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116438069B_ABST
    Figure CN116438069B_ABST
Patent Text Reader

Abstract

Provided is a fiber-reinforced resin that can be fused with other components via a thermoplastic resin and that is less likely to be damaged even when fusion is performed at high temperatures. A fiber-reinforced resin includes a reinforcing fiber and has an epoxy resin cured product region and a thermoplastic resin region formed on a surface, wherein the proportion of aromatic rings in the epoxy resin cured product constituting the epoxy resin cured product region is 50% or greater but 90% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to fiber-reinforced resins and integrally molded articles formed by fusing fiber-reinforced resins with other components. Background Technology

[0002] Fiber-reinforced resins, which use thermosetting resins such as epoxy resin as the matrix and combine them with reinforcing fibers such as carbon fiber and glass fiber, are not only lightweight but also possess excellent mechanical properties such as strength and rigidity, as well as heat resistance and corrosion resistance. Therefore, they are increasingly being used in numerous fields, including aerospace, automotive, railway vehicles, shipbuilding, civil engineering, sporting goods, and electronic components. On the other hand, fiber-reinforced resins using thermosetting resins are not suitable for molding complex shapes. To manufacture components and structures with complex shapes, it is necessary to integrate a relatively simple fiber-reinforced resin component with other components (hereinafter referred to as "other components") made of the same or different types of fiber-reinforced resin.

[0003] Methods for integrating fiber-reinforced resin with other components include mechanical joining methods such as bolts, rivets, and screws, as well as joining methods using adhesives. However, mechanical joining methods require pre-processing of the joining parts, such as drilling, which leads to longer manufacturing processes, increased manufacturing costs, and reduced material strength due to processing. Adhesive-based joining methods involve adhesive preparation, application, and curing, resulting in longer manufacturing processes and difficulties in achieving sufficient bond strength reliability.

[0004] As a solution to this problem, fiber-reinforced resins with a thermoplastic resin layer formed on the surface of the fiber-reinforced resin using thermosetting resins have been developed in recent years (Patent Document 1). Such fiber-reinforced resins can be easily bonded to other components by means of the fusion of the thermoplastic resin layer.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2004 / 060658 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] In particular, in applications requiring heat resistance, when using high-melting-point resins such as super engineering plastics as the fiber-reinforced thermoplastic resin layer forming this thermoplastic resin layer, temperatures exceeding 300°C are required for welding with other components. At this temperature, the surrounding epoxy resin will also be exposed to temperatures above 300°C. Since epoxy resin tends to decompose rapidly from around 300°C, welding at temperatures near 300°C carries the risk of damage caused by epoxy resin decomposition.

[0010] The object of the present invention is to provide a fiber-reinforced resin that can be welded to other components by means of a thermoplastic resin and is not easily damaged even when such welding is carried out at high temperatures.

[0011] Methods for solving problems

[0012] To solve the above-mentioned problems, the fiber-reinforced resin of the present invention is a fiber-reinforced resin comprising reinforcing fibers and having an epoxy resin cured region and a thermoplastic resin region formed on the surface, wherein the proportion of aromatic rings in the epoxy resin cured region constituting the aforementioned epoxy resin cured region is 50% or more and 90% or less.

[0013] Invention Effects

[0014] By using the fiber-reinforced resin of the present invention, damage is less likely to occur when the thermoplastic resin area is welded to other components, and it is possible to produce an integrally molded article with excellent tensile shear bond strength. Attached Figure Description

[0015] [ Figure 1 [Illustration] is a schematic diagram of a cross section perpendicular to the surface of the fiber-reinforced resin of the present invention, which helps to illustrate the method for measuring the roughness mean length RSm and the roughness mean height Rc described later. Detailed Implementation

[0016] In this specification, “~” indicates a range of values ​​including both ends of the value.

[0017] The fiber-reinforced resin of the present invention comprises reinforcing fibers and has an epoxy resin cured region and a thermoplastic resin region formed on the surface, wherein the proportion of aromatic rings in all molecules constituting the epoxy resin cured product is 50% to 90% and the epoxy resin cured product is the epoxy resin cured product constituting the aforementioned epoxy resin cured product region.

[0018] The fiber-reinforced resin of the present invention, by having thermoplastic resin regions formed on its surface, enables other components to be fused to these thermoplastic resin regions, thereby producing an integrally molded article. It should be noted that "other components" is not particularly limited and can include components comprising thermoplastic resin, components formed of metal materials, and the fiber-reinforced resin of the present invention. It should also be noted that sometimes, other components fused to the surface thermoplastic resin regions of the fiber-reinforced resin of the present invention to form an integrally molded article are referred to as adherends. Thermoplastic resins included in this thermoplastic resin category are not particularly limited, and examples include: polyester resins (polyethylene terephthalate, polybutylene terephthalate, polypropylene terephthalate, polyethylene naphthalate, liquid crystal polyester, etc.), polyolefin resins (polyethylene, polypropylene, polybutene, etc.), styrene resins, urethane resins, as well as polyoxymethylene, polyamide resins (aliphatic polyamides such as polyamide 6 and polyamide 66, semi-aromatic polyamides, alicyclic polyamides, etc.), polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamide imide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyketone, polyarylene ether ketone (polyether ketone, polyether ether ketone, polyether ketone ketone, etc.), polyarylates, polyether nitrile, phenolic resins, phenoxy resins, etc. Furthermore, these thermoplastic resins may also be copolymers, modifiers, and / or blends of two or more of the aforementioned resins. Among these, from the viewpoint of obtaining fiber-reinforced resins with excellent heat resistance, polyketones, polyetherketones, polyetheretherketones, polyetherketones, polyetherketoneketones, and other polyarylene ether ketones, alicyclic polyamides, semi-aromatic polyamides, polyphenylene sulfide, polyetherimide, polyethersulfone, polysulfone, modified polysulfone, and polyamide imide are particularly preferred.

[0019] In particular, in the fiber-reinforced resin of the present invention, it is preferable that the epoxy resin cured region (described later) and the surface thermoplastic resin region each form layers that are adjacent to each other. The term "forming layers that are adjacent to each other" means, for example, as... Figure 1 As shown, in a cross-section obtained by cutting perpendicular to the plane of the prepreg blank, the continuous thermoplastic resin region 2 and the epoxy resin cured region 3 in the surface direction form a boundary surface 5 and exist in close contact. When the thermoplastic resin exists not in a continuous layered state, but in a particulate, fibrous, or nonwoven fabric state, the proportion of the epoxy resin exposed on the surface increases, and the coverage of the thermoplastic resin on the outermost surface decreases, thus tending to reduce weldability.

[0020] The unit area weight of the thermoplastic resin region is 10 g / m² 2 When the above conditions are met, excellent bonding strength with the adherend is exhibited, therefore it is preferred. The weight per unit area of ​​the thermoplastic resin region is more preferably 20 g / m². 2There is no specific upper limit, but in order to ensure that the amount of thermoplastic resin does not become excessive compared to the reinforcing fibers, and to obtain fiber-reinforced resin with excellent specific strength and specific modulus of elasticity, the unit area weight of the thermoplastic resin region is preferably 500 g / m². 2 Below. Here, the weight per unit area of ​​the thermoplastic resin region refers to the weight per 1m². 2 The mass (g) of thermoplastic resin constituting the thermoplastic resin region contained in the fiber-reinforced resin.

[0021] The reinforcing fibers contained in the fiber-reinforced resin of the present invention can be glass fibers, carbon fibers, metal fibers, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, basalt fibers, etc. They can be used alone or in combination of two or more.

[0022] As reinforcing fibers, carbon fibers with low specific gravity, high strength, and high elastic modulus are preferred. Commercially available carbon fibers include Torayca T800G-24K, Torayca T800S-24K, Torayca T700G-24K, Torayca T700S-24K, Torayca T300-3K, Torayca T1100G-24K, Torayca M30S-18K, Torayca M40J-12K, and Torayca M60J-6K (all manufactured by Toray Industries, Inc.).

[0023] The thermal conductivity of the reinforcing fibers used in the fiber-reinforced resin of the present invention is preferably 100 W / (m·K) or less. When the thermal conductivity of the reinforcing fibers is 100 W / (m·K) or less, the heat transferred to the cured epoxy resin in the fiber-reinforced resin is suppressed when heat is applied to the fiber-reinforced resin during welding, and the thermal decomposition of the epoxy resin is suppressed, thus making it a preferred method. Carbon fiber is more preferably the reinforcing fiber having the above-mentioned thermal conductivity. The above-mentioned thermal conductivity is more preferably 50 W / (m·K) or less, and even more preferably 30 W / (m·K) or less. There is no particular limitation on the lower limit of the thermal conductivity of the reinforcing fibers; if it is ordinary carbon fiber, the lower limit is 3 W / (m·K).

[0024] Furthermore, when the tensile strength of the reinforcing fibers used in the fiber-reinforced resin of the present invention, as determined by the resin impregnation wire harness test method according to JIS R7608 (2007), is 5.5 GPa or higher, a fiber-reinforced resin exhibiting excellent bonding strength in addition to tensile strength can be obtained, which is therefore preferred. It is even more preferred if the tensile strength of the wire harness is 5.8 GPa or higher. The bonding strength referred to here is the bonding strength when joined to other components by fusion welding through the thermoplastic resin region of the surface, and is the tensile shear bond strength determined according to ISO 4587:1995 (JIS K6850 (1994)).

[0025] These reinforcing fibers can also be surface-treated fibers. Surface treatments include metal bonding treatment, treatment using coupling agents, treatment using sizing agents, and additive attachment treatment.

[0026] Specifically, as a reinforcing fiber, a surface free energy of 10 mJ / m, as determined by the Wilhelmy method, is used. 2 Above 50mJ / m 2 The following reinforcing fibers are preferred. By controlling the range, the aforementioned reinforcing fibers exhibit high affinity with the aforementioned epoxy resin and the aforementioned thermoplastic resin, and exhibit excellent tensile shear bond strength when bonded to other components via fusion welding through the surface thermoplastic resin region. Furthermore, by suppressing the aggregation of the aforementioned reinforcing fibers, the dispersion of the reinforcing fibers in the molded article becomes better, and the deviation (coefficient of variation) of the tensile shear bond strength is reduced. The surface free energy of the aforementioned reinforcing fibers is preferably 15 mJ / m. 2 Above 40mJ / m 2 The preferred value is 18 mJ / m 2 Above 35mJ / m 2 The following are methods for controlling the surface free energy of the aforementioned reinforcing fibers: methods that control the amount of oxygen-containing functional groups such as carboxyl and hydroxyl groups by oxidizing the surface; and methods that control the surface by attaching one or more compounds to the surface. When attaching multiple compounds to the surface, compounds with high surface free energy and compounds with low surface free energy can be mixed and attached. The surface free energy can be calculated by measuring the contact angles of the reinforcing fibers with three solvents (purified water, ethylene glycol, and tricresyl phosphate) and then calculating the surface free energy using the Owens approximation formula. The steps are shown below, but the measuring equipment and detailed methods are not limited to the following.

[0027] Using a DataPhysics DCAT11, first, a single fiber is taken from the reinforcing fiber bundle and cut into eight fibers, each 12 ± 2 mm in length. These fibers are then attached parallel to each other at a distance of 2–3 mm to a dedicated retainer FH12 (a flat plate coated with an adhesive). Next, the tips of the fibers are trimmed and placed on the DCAT11 retainer. Measurements are performed as follows: a tank containing each solvent is brought close to the lower ends of the eight fibers at a speed of 0.2 mm / s, immersing them to a point 5 mm from the tip of each fiber. Then, the fibers are pulled up at a speed of 0.2 mm / s. This operation is repeated at least four times. The force F experienced by the fiber while immersed in the liquid is measured using an electronic balance. This value is used to calculate the contact angle θ according to the following formula.

[0028] COSθ = (Force F (mN) on 8 single fibers) / (8 (number of single fibers) × circumference of single fiber (m) × surface tension of solvent (mJ / m) 2 ))

[0029] It should be noted that measurements were performed on individual fibers extracted from different positions within the three reinforcing fiber bundles. That is, the average contact angle of a total of 24 individual fibers from a single reinforcing fiber bundle was calculated.

[0030] Surface free energy γ of reinforcing fiber f γ, the polar component of surface free energy p f and the nonpolar component of surface free energy γ d f The surface free energy is calculated by summing the components of the surface tension and the contact angle of each liquid into the Owens approximation formula shown below (an formula composed of the polar and non-polar components of the inherent surface tension of each solvent and the contact angle θ), plotted on X and Y, and then obtained by the square of the slope 'a' when performing a linear fit using the least squares method. The non-polar component of the surface free energy is γ. d f It is obtained by squared the intercept b. The surface free energy γ of the reinforcing fiber is... f It is the sum of the square of the slope a and the square of the intercept b.

[0031] Y = a·X + b

[0032] X = √(the polar component of the solvent's surface tension (mJ / m)) 2 )) / √(The nonpolar component of the solvent's surface tension (mJ / m 2 )

[0033] Y = (1 + Cosθ)·(polar component of the surface tension of the solvent (mJ / m)) 2)) / 2√(Nonpolar component of solvent surface tension (mJ / m 2 )

[0034] The polar component γ of the surface free energy of reinforcing fibers p f =a 2

[0035] The nonpolar component γ of the surface free energy of the reinforcing fiber d f =b 2

[0036] Total surface free energy γ f =a 2 +b 2 .

[0037] The polar and non-polar components of the surface tension of each solvent are described below.

[0038] Purified water

[0039] Surface tension 72.8 mJ / m 2 Polar component 51.0 mJ / m 2 Nonpolar component 21.8 (mJ / m 2 )

[0040] · Ethylene glycol

[0041] Surface tension 48.0 mJ / m 2 Polar component 19.0 mJ / m 2 Nonpolar component 29.0 (mJ / m 2 )

[0042] Tricresol phosphate

[0043] Surface tension 40.9 mJ / m 2 Polar component 1.7 mJ / m 2 Nonpolar component 39.2 (mJ / m 2 ).

[0044] Regarding the morphology and arrangement of the reinforcing fibers, appropriate choices can be made from: unidirectional arrangement of the reinforcing fibers; laminates of objects formed by unidirectional arrangement of reinforcing fibers; or woven fabrics, knitted fabrics, nonwoven fabrics, felts, braided tapes, etc. However, to obtain fiber-reinforced resins with higher levels of lightweight and durability, the morphology of long fibers (fiber bundles) or continuous fibers such as woven fabrics formed by unidirectional arrangement of reinforcing fibers is preferred in each prepreg preform. Furthermore, from the viewpoint of shapeability and shape conformability during molding, the morphology of nonwoven fabrics or felts using discontinuous reinforcing fibers is also preferred.

[0045] The fiber-reinforced resin of the present invention preferably has a reinforcing fiber content of 30% by mass or more and 90% by mass or less, more preferably 35% by mass or more and 85% by mass or less, and even more preferably 40% by mass or more and 80% by mass or less. When the reinforcing fiber content is 30% by mass or more, the amount of resin does not become excessive compared to the amount of fiber, making it easier to obtain a fiber-reinforced resin with excellent specific strength and specific modulus of elasticity. Furthermore, when the reinforcing fiber content is 90% by mass or less, poor resin impregnation is less likely to occur, and the porosity of the obtained fiber-reinforced resin is more likely to be reduced.

[0046] In the epoxy resin cured product constituting the fiber-reinforced resin of the present invention, the aromatic ring content is 50% to 90%. When the aromatic ring content is less than 50%, the epoxy resin cured product is prone to thermal decomposition at high temperatures, resulting in a significant decrease in mechanical properties such as compressive strength as a fiber-reinforced resin, as well as tensile shear bond strength when fused with other components. When the aromatic ring content is 90% or more, the flexibility of the epoxy resin cured product is impaired, thus reducing its mechanical properties as a fiber-reinforced resin. An aromatic ring content of 55% to 80% is more preferable in the epoxy resin cured product.

[0047] The aromatic ring ratio of the epoxy resin cured product in this specification refers to the mass ratio of aromatic rings constituting the chemical structure of the epoxy resin cured product, calculated by dividing the total mass of all aromatic rings in the total chemical structural formula by the total mass of all molecules in the total chemical structural formula. It should be noted that when substituents such as methyl groups are present in the aromatic rings, the mass of the aromatic rings does not include the mass of the substituents. For example, the structure of benzene is calculated based on an aromatic ring mass of 78.1 g / mol, and the structure of toluene is calculated based on an aromatic ring mass of 77.1 g / mol.

[0048] When the chemical structures of each compound constituting the epoxy resin composition in its pre-cured state as a cured epoxy resin product are known, the aromatic ring ratio of the cured epoxy resin product can be calculated from these chemical structures. Furthermore, if the chemical structures are unknown, they can be calculated by identifying the chemical structure of the cured epoxy resin product using pyrolysis gas chromatography-mass spectrometry. Additionally, as an example, when the cured epoxy resin product is composed of the chemical structures of the following formulas (1) and (2), and the molecular proportions are 70% and 30% of the total, respectively, the aromatic ring ratio of the cured epoxy resin product becomes:

[0049] (76.1×4×0.70+(126.2+76.1×2)×0.3) /

[0050] (676.9×0.7+522.6×0.3)=47.1%.

[0051] [Chemical Formula 1]

[0052]

[0053] [Chemical Formula 2]

[0054]

[0055] From the perspective of improving resistance to pyrolysis at high temperatures, it is preferable that the epoxy resin cured product of the present invention is a cured product of an epoxy resin composition comprising an epoxy resin having a polycyclic aromatic hydrocarbon backbone or a biphenyl backbone.

[0056] Epoxy resins with a polycyclic aromatic hydrocarbon backbone include those with a naphthalene backbone, an anthracene backbone, a phenanthrene backbone, a pyrene backbone, and a tetraphenylene backbone. Examples include naphthylene ether type epoxy resins, naphthalene glycol type epoxy resins, methylene dinaphthol type epoxy resins, dinaphthol type epoxy resins, naphthol phenyl aralkyl type epoxy resins, naphthol biphenyl aralkyl type epoxy resins, and anthracene glycol type epoxy resins. Epoxy resins with a biphenyl backbone include biphenyl diglycidyl ether and phenol biphenyl aralkyl type epoxy resins.

[0057] Furthermore, the epoxy resin cured product of the present invention is a cured product of an epoxy resin composition in which the average epoxy equivalent of all epoxy resins is 160 g / eq. or more and 255 g / eq. or less. This is preferred for improving resistance to thermal decomposition at high temperatures and exhibiting excellent glass transition temperature. An average epoxy equivalent of 180 g / eq. or more and 255 g / eq. or less is more preferred. Here, as an example, in the case of containing both epoxy resin 1 and epoxy resin 2, the average epoxy equivalent is calculated as follows. It should be noted that in this specification, epoxy equivalent refers to the value obtained by the method described in JIS K7236 (2009).

[0058] Average epoxy equivalent (g / eq.) = (mass parts of epoxy resin 1 × epoxy equivalent of epoxy resin 1 + mass parts of epoxy resin 2 × epoxy equivalent of epoxy resin 2) / (mass parts of epoxy resin 1 + mass parts of epoxy resin 2)

[0059] Furthermore, the same calculation method applies when there are three or more epoxy resin components. When there are N epoxy resin components from epoxy resin 1 to epoxy resin N, the calculation is performed as follows.

[0060] Average epoxy equivalent (g / eq.) = (mass parts of epoxy resin 1 × epoxy equivalent of epoxy resin 1 + mass parts of epoxy resin 2 × epoxy equivalent of epoxy resin 2 + ... + mass parts of epoxy resin N × epoxy equivalent of epoxy resin N) / (mass parts of epoxy resin 1 + mass parts of epoxy resin 2 + ... + mass parts of epoxy resin N)

[0061] The epoxy resin cured product of this invention is a cured product containing a polyamine compound with an average active hydrogen equivalent of 55 g / eq. to 100 g / eq., thereby improving its resistance to thermal decomposition at high temperatures, and is therefore preferred. In this specification, the term "polyamine compound" refers to a general term for compounds having two or more amino groups, such as dicyandiamide, aliphatic amine compounds, aromatic amine compounds, tetramethylguanidine, thiourea addition amines, and carboxylic acid hydrazides. It should be noted that, in this specification, the active hydrogen equivalent of the polyamine compound refers to the active hydrogen equivalent calculated by identifying the chemical structure and its proportion using liquid chromatography-mass spectrometry (LC / MS). Here, as an example, in the case containing both polyamine compound 1 and polyamine compound 2, the average active hydrogen equivalent is calculated as follows.

[0062] Average active hydrogen equivalent (g / eq.) = (mass parts of polyamine compound 1 × active hydrogen equivalent of polyamine compound + mass parts of polyamine compound 2 × active hydrogen equivalent of polyamine compound 2) / (mass parts of polyamine compound 1 + mass parts of polyamine compound 2)

[0063] In the case of polyamine compounds containing three or more components, the calculations can be performed in the same manner as in the case of epoxy resins described above.

[0064] In the case of epoxy resins other than those with a polycyclic aromatic hydrocarbon backbone or a biphenyl backbone, examples of such epoxy resins include bisphenol-type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, and bisphenol S type epoxy resin; brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether; epoxy resins with a dicyclopentadiene backbone; Novolac-type epoxy resins such as phenol Novolac type epoxy resin and cresol Novolac type epoxy resin; and N,N,O-triglycidyl-m-aminophenol. Glycidylamine type epoxy resins such as N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenediphenylamine, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenediphenylamine, N,N,N',N'-tetraglycidyl-m-phenylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, and triglycidyl isocyanurate, etc.

[0065] As polyamine compounds, aromatic amine compounds having two or more amino groups are preferred because they exhibit good reactivity and excellent mechanical properties and heat resistance as cured products. Examples of aromatic amine compounds having two or more amino groups include diaminodiphenyl sulfone, diaminobenzoylaniline, diaminobenzophenone, diaminodiphenylmethane, and their isomers, as well as adducts of aliphatic hydrocarbons and halogen groups.

[0066] The epoxy resin cured product of the fiber-reinforced resin of the present invention is preferably a cured product of an epoxy resin composition having a heat loss rate of 1.0% or less when the cured product obtained by heating at 180°C for 120 minutes is held at 300°C for 2 minutes. Furthermore, it is preferable to be a cured product of an epoxy resin composition having a glass transition temperature of 180°C or higher and 350°C or lower. By giving the cured product such properties, damage during welding can be suppressed when the thermoplastic resin layer on the surface of the fiber-reinforced resin is fused to other components. A more preferred heat loss rate is 0.7% or less, and even more preferably 0.5% or less when held at 300°C for 2 minutes.

[0067] The thermal mass reduction rate of epoxy resin cured products can be determined based on JIS K7120 (1987). Furthermore, the glass transition temperature can be determined based on JIS K7244-7 (2007).

[0068] In the fiber-reinforced resin of the present invention, it is preferable that the average roughness length RSm of the boundary surface between the aforementioned epoxy resin cured region and the aforementioned thermoplastic resin region is 100 μm or less and the average roughness height Rc is 3.5 μm or more. Here, the average roughness length RSm and the average roughness height Rc of the boundary surface between the aforementioned epoxy resin cured region and the aforementioned thermoplastic resin region are defined as the average roughness length RSm and the average roughness height Rc of the interface curve formed by the closely adhering boundary surfaces of the two resin regions in a cross section obtained by cutting perpendicular to the plane direction of the fiber-reinforced resin, as defined by JIS B0601 (2001). When the average roughness length RSm of the interface curve is 100 μm or less, not only chemical and / or physical bonding forces are applied, but also mechanical bonding forces such as interlacing are applied, and the epoxy resin cured region and the resin region containing the thermoplastic resin are not easily separated, which is therefore preferable. The lower limit value of RSm is not particularly limited, but from the viewpoint of avoiding the reduction of mechanical bonding force caused by stress concentration, it is preferably 15 μm or more. Furthermore, by setting the average roughness height Rc of the interface curve to 3.5 μm or more, not only is mechanical bonding based on interlacing exhibited, but the reinforcing fibers present at the boundary surface also chemically and / or physically bond with the epoxy resin and thermoplastic resin, thus improving the adhesion between the epoxy resin cured region and the resin region containing the thermoplastic resin, which is therefore preferable. A more preferred range for the average roughness height Rc of the interface curve is 10 μm or more, particularly preferably 20 μm or more, where the reinforcing fibers readily connect with the two resin regions and the adhesion is further improved. While there is no particular upper limit to Rc, from the viewpoint of avoiding a decrease in mechanical bonding strength due to stress concentration, 100 μm or less is preferred.

[0069] Here, known methods can be used to determine the average roughness height Rc and average roughness length RSm of the interface curve. Examples include: methods using cross-sectional images obtained via X-ray CT; methods using elemental analysis mapping images obtained via energy dispersive X-ray spectrometer (EDS); or methods using cross-sectional observation images obtained via optical microscope, scanning electron microscope (SEM), or transmission electron microscope (TEM). During observation, epoxy resin and / or thermoplastic resin may be stained to adjust contrast. In the images obtained by any of the above methods, the average roughness height Rc and average roughness length RSm of the interface curve are measured within a 500 μm square area.

[0070] use Figure 1An example of a method for measuring the average roughness height Rc and average roughness length RSm of an interface curve is presented (Method 1 for measuring interface curve elements). Using the end 6 of the epoxy resin cured region side of the rectangular observation image 4 as a reference line, vertical baselines 7 are drawn from the epoxy resin cured region 3 to the thermoplastic resin region 2 at 5 μm intervals. The point where the vertical baseline drawn from the reference line first intersects with the thermoplastic resin region 2 is plotted, and the line connecting the plotted points is designated as the interface curve 8. For the obtained interface curve 8, a screening process based on JIS B0601 (2001) is performed, and the average roughness height Rc and average roughness length RSm of the interface curve 8 are calculated.

[0071] Furthermore, regarding the fiber-reinforced resin of the present invention, it is preferable that there are reinforcing fibers that cross the boundary between the aforementioned epoxy resin cured region and the aforementioned thermoplastic resin region and are in contact with both resin regions. The presence of such reinforcing fibers can be confirmed by observing a cross-section obtained by cutting perpendicular to the planar direction. For example, in Figure 1 In the cross-sectional observation image 4 shown, multiple reinforcing fibers 1 are present on the boundary surface 5 between the thermoplastic resin region 2 and the epoxy resin cured region 3. The reinforcing fibers 1 on the boundary surface 5 are in contact with both the thermoplastic resin region 2 and the epoxy resin cured region 3. This state of contact between the thermoplastic resin and the epoxy resin and the surrounding area of ​​the reinforcing fibers can be described as a state in which the reinforcing fibers "cross the boundary surface and contact these two resin regions".

[0072] The presence of reinforcing fibers that cross the boundary between the epoxy resin cured region and the thermoplastic resin region, thus connecting with both resin regions, increases the strength of the thermoplastic resin region and improves the bond strength. Furthermore, the chemical and / or physical bonding between the reinforcing fibers crossing the boundary and the heat-cured epoxy resin and thermoplastic resin further enhances the adhesion between the heat-cured epoxy resin region and the thermoplastic resin region, resulting in increased bond strength.

[0073] For the fiber-reinforced resin of the present invention, in order to improve impact resistance, elastomers or rubber components may be added to the epoxy resin cured product or thermoplastic resin. Furthermore, depending on the application, the epoxy resin cured product or thermoplastic resin may appropriately contain other fillers and additives without prejudice to the purpose of the present invention. Examples of such fillers include: inorganic fillers, flame retardants, conductivity imparting agents, nucleating agents, ultraviolet absorbers, antioxidants, vibration damping agents, antibacterial agents, insect repellents, deodorizers, anti-staining agents, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, defoamers, coupling agents, etc.

[0074] One example of the method for manufacturing the fiber-reinforced resin of the present invention is by means of a prepreg preform containing an epoxy resin composition prior to curing and reinforcing fibers, and having a thermoplastic resin region on its surface, and which is laminated together with other prepreg preforms as needed, and then subjected to pressure and heating to cure it. For example, compression molding, autoclave molding, bag molding, wrapping, internal pressure molding, and hand lay-up molding can be used for the pressure and heating method. Other examples of methods for manufacturing the fiber-reinforced resin of the present invention include filament winding, pultrusion molding, resin injection molding, and resin transfer molding.

[0075] Furthermore, the integral molded article of the present invention is formed by fusing the fiber-reinforced resin of the present invention with other components through the aforementioned thermoplastic resin region. By forming a molded article by fusing the thermoplastic resin region with other components, the bonding portion between the fiber-reinforced resin portion and other components has excellent tensile shear bond strength.

[0076] Example

[0077] The present invention will now be described in detail using examples. However, the scope of the present invention is not limited to these examples. It should be noted that the unit "parts" for composition ratios refers to parts by mass unless otherwise specified. Furthermore, all measurements are conducted at an environment of 23°C and 50% relative humidity unless otherwise specified.

[0078] <Materials used in the Examples and Comparative Examples>

[0079] [Epoxy Resin]

[0080] • Naphthyl ether type epoxy resin (“EPICLON” (registered trademark) HP-6000, manufactured by DIC Corporation, epoxy equivalent: 250g / eq.)

[0081] • Biphenyl aralkyl type epoxy resin (NC-3000, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 275 g / eq.)

[0082] • Tetraglycidyl diaminodiphenylmethane (“Sumiepoxy” (registered trademark) ELM434, manufactured by Sumitomo Chemical Co., Ltd., epoxy equivalent: 120 g / eq.)

[0083] • Bisphenol F type epoxy resin (“EPICLON” (registered trademark) 830, manufactured by DIC Corporation, epoxy equivalent: 172 (g / eq.))

[0084] • Naphthol phenyl aralkyl type epoxy resin (NC-7000L, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 230g / eq.).

[0085] [Polyamine compounds]

[0086] ·4,4'-Diaminodiphenyl sulfone (Seikacure S, manufactured by Wakayama Seika Kogyo Co., Ltd., active hydrogen equivalent: 62 g / eq.).

[0087] [Viscosity modifier (thermoplastic resin soluble in epoxy resin)]

[0088] • Polyethersulfone (“Sumikaexcel” (registered trademark) PES5003P manufactured by Sumitomo Chemical Co., Ltd.).

[0089] [Reinforcing Fibers]

[0090] Referring to Japanese Patent Application Publication No. 2010-255168, a copolymer of acrylonitrile with itaconic acid was spun and sintered to obtain carbon fibers 1 to 4 with different thermal conductivity (before sizing agent coating). A 1% by mass solution of sizing agent compound 1 was prepared by mixing and dissolving it in acetone. Each compound was then coated onto the carbon fibers 1 to 4 using an impregnation method, followed by heat treatment at 210°C for 90 seconds. The amount of each compound was adjusted to be 0.5 parts by mass relative to 100 parts by mass of the carbon fibers to which each compound was attached, resulting in a surface free energy of 20 mJ / m. 2 Carbon fibers 1 to 4. The properties of each carbon fiber are as follows.

[0091] • Carbon fiber 1: Tensile strength of the wire harness is 5.9 GPa, tensile modulus of elasticity of the wire harness is 294 GPa, and thermal conductivity is 10 W / (m·K).

[0092] • Carbon fiber 2: Tensile strength of the wire harness is 5.5 GPa, tensile modulus of elasticity of the wire harness is 294 GPa, and thermal conductivity is 22 W / (m·K).

[0093] • Carbon fiber 3: Tensile strength of the wire harness is 4.4 GPa, tensile modulus of elasticity of the wire harness is 377 GPa, and thermal conductivity is 69 W / (m·K).

[0094] • Carbon fiber 4: Tensile strength of the wire harness is 4.1 GPa, tensile modulus of elasticity of the wire harness is 475 GPa, and thermal conductivity is 105 W / (m·K).

[0095] In addition, carbon fibers with different surface free energies were obtained by attaching sizing agent compounds 2 to 6 to carbon fiber 1 (before sizing agent coating) using the same method as described above.

[0096] The following are the compounds used as sizing agents for various carbon fibers and the surface free energy after sizing agent coating.

[0097] • Compound 1 for sizing agent: Polyethylene glycol diglycidyl ether (“Denacol” (registered trademark) EX-841, manufactured by Nagase ChemteX Corporation), surface free energy: 20 mJ / m 2

[0098] • Compound 2 for sizing agents: Bisphenol A type diglycidyl ether (“jER” (registered trademark) 828, manufactured by Mitsubishi Chemical Corporation), surface free energy: 9 mJ / m 2

[0099] • Compound 3 for sizing agents: Sorbitol polyglycidyl ether (“Denacol” (registered trademark) EX-614B, manufactured by Nagase ChemteX Corporation), surface free energy: 32 mJ / m 2

[0100] • Compound 4 for sizing agent: 24 molar adduct of bisphenol A and propylene oxide, surface free energy: 18 mJ / m 2

[0101] Compound 5 for sizing agents: polyallylamine (PAA-01, manufactured by Nippon Shokubai Co., Ltd.), surface free energy: 32 mJ / m 2

[0102] Compound 6 for sizing agents: Polyethyleneimine (SP-012, manufactured by Nippon Shokubai Co., Ltd.), surface free energy: 33 mJ / m 2

[0103] [Thermoplastic resin]

[0104] • PPS: 120 g / m² of polyphenylene sulfide (“Torelina” (registered trademark) A900 (manufactured by Toray Industries, Inc., melting point 278°C, glass transition temperature 92°C) per unit area. 2 membrane

[0105] • PEEK: Polyetheretherketone (PEEK 450G (manufactured by Victrex, melting point 343℃, glass transition temperature 143℃)) has a unit area weight of 120 g / m². 2 membrane

[0106] • PEKK: Polyetherketoneketone (“KEPSTAN” (registered trademark) 6002 (manufactured by Arkema, melting point 300℃, glass transition temperature 160℃)) with a unit area weight of 120 g / m². 2 membrane

[0107] • PEI: A polyetherimide (“ULTEM” (registered trademark), manufactured by SABIC, with a glass transition temperature of 217°C) having a unit area weight of 120 g / m². 2 membrane

[0108] • Semi-aromatic PA: 120 g / m² formed from polyamide 6T (melting point 320℃, glass transition temperature 125℃). 2 membrane.

[0109] It should be noted that the melting point of the thermoplastic resin is based on JIS K7121 (2012) and determined using a differential scanning calorimeter (DSC). In cases where multiple melting points are observed in mixtures, the highest melting point is taken as the melting point of the thermoplastic resin.

[0110] <Evaluation Methods>

[0111] [Properties of Cured Epoxy Resins]

[0112] The epoxy resin compositions prepared by the reference examples described below were injected into a mold and heated in a hot air dryer from 30°C to 180°C at a rate of 1.5°C / min. After curing for 120 minutes, the temperature was lowered to 30°C at a rate of 2.5°C / min to produce a plate-shaped cured epoxy resin product with a thickness of 2 mm.

[0113] From the resin-cured plate prepared by the above method, test pieces with a width of 12.7 mm and a length of 45 mm were cut out. The test pieces were dried in a vacuum oven at 60°C for 24 hours. The storage modulus curve was obtained by dynamic viscoelasticity test according to JIS K7244-7(2007). In the above storage modulus curve, the temperature at the intersection of the tangent in the glass state and the tangent in the transition state was set as the glass transition temperature.

[0114] Furthermore, the plate-shaped cured resin prepared by the above method was pulverized, and approximately 10 mg of evaluation sample was collected. The rate of decrease in thermal mass was determined using a differential gravimetric analyzer according to JIS K7120 (1987). In all measurements, air was used as the inflow gas. The evaluation of the rate of decrease in thermal mass when heated from room temperature to 300°C and from room temperature to 350°C was conducted at a heating rate of 50°C / min and a measurement temperature range of 25°C to 400°C. The rate of decrease in mass at 300°C or 350°C was measured. In isothermal measurements, the temperature was increased from 200°C, and after reaching 300°C, it was held at 300°C for 2 minutes, and the rate of decrease in thermal mass was measured.

[0115] [Structural observation of fiber-reinforced resin]

[0116] In the observation section obtained by cutting the fiber-reinforced resin perpendicular to the plane direction, an image at 1000x magnification is captured using an optical microscope. In the obtained image, if the reinforcing fiber exists at the boundary between the thermoplastic resin region and the epoxy resin cured region, and the reinforcing fiber is in contact with both the thermoplastic resin region and the epoxy resin cured region, it is considered to be in a state where "the reinforcing fiber is in contact with both resin regions in a manner that crosses the boundary." Within any 500 μm square observation range in the obtained image, the roughness average length RSm and roughness average height Rc of the obtained interface curve elements are measured using the aforementioned method 1 for measuring interface curve elements, as defined by JIS B0601 (2001).

[0117] [Compressive strength of fiber-reinforced resin]

[0118] After bonding the tabs to the fiber-reinforced resin according to SACMA-SRM 1R-94, rectangular test pieces with a length of 80 mm and a width of 15 mm were cut, with the reinforcing fiber axis as the length direction of the test piece. The obtained test pieces were dried in a vacuum oven at 60°C for 24 hours. Under the following three test conditions, the compressive strength was determined using a universal testing machine (Instron Japan Company, Ltd., "Instron" (registered trademark) 5565 model P8564) according to SACMA-SRM 1R-94.

[0119] 1) The compressive strength was measured at 23°C without any treatment of the test pieces. (Untreated condition)

[0120] 2) After being subjected to high-temperature exposure treatment by holding the test piece with a hot plate at 300°C for 2 minutes, the compressive strength was measured at 23°C.

[0121] 3) After undergoing a water absorption treatment by immersing in hot water at 71°C for 14 days, the compressive strength was measured at a high temperature of 120°C.

[0122] Based on the measurement results in 2) above, the following evaluation was conducted. The results are shown in Tables 2 to 6.

[0123] 1.4GPa and above: A

[0124] Above 1.2 GPa and below 1.4 GPa: B

[0125] Above 1.0 GPa and below 1.2 GPa: C

[0126] Less than 1.0 GPa: D (Unqualified)

[0127] Furthermore, based on the measurement results in 3) above, the following evaluation was conducted. The results are shown in Tables 2 to 6.

[0128] Above 1.2 GPa: A

[0129] Above 1.0 GPa and below 1.2 GPa: B

[0130] Above 0.8 GPa and below 1.0 GPa: C

[0131] Less than 0.8 GPa: D (Unqualified)

[0132] Tensile shear bond strength of unibody molded products

[0133] According to ISO 4587:1995 (JIS K6850 (1994)), the winglets are bonded to the manufactured integral molded part and cut to a width of 25 mm to obtain the target test piece.

[0134] The obtained test pieces were dried in a vacuum oven for 24 hours. The tensile shear bond strength was determined at an ambient temperature of 23°C according to ISO 4587:1995 (JIS K6850 (1994)). Based on the test results, the following evaluation was conducted. The coefficient of variation was calculated by dividing the standard deviation by the average of five tensile shear bond strength measurements. The results are shown in Tables 2–6.

[0135] Above 28MPa: A

[0136] 25MPa or higher but less than 28MPa: B

[0137] Above 20MPa and below 25MPa: C

[0138] Less than 20MPa: D (Unqualified).

[0139] <Reference Examples 1-7: Preparation of Epoxy Resin Compositions>

[0140] The epoxy resin, polyamine compound, and viscosity modifier listed in Table 1 were added to a mixing apparatus and heated to mix, causing the viscosity modifier to dissolve. It should be noted that the figures for these compositions in Table 1 represent parts by mass when the total epoxy resin is 100 parts by mass. Next, while continuing to mix, the temperature was lowered to below 100°C, and substances appropriately selected from the polyamine compound and other curing agents listed in Table 1 were added and stirred to obtain the epoxy resin compositions referred to as Reference Examples 1 to 7.

[0141] [Table 1]

[0142]

[0143] <Fabrication of Fiber-Reinforced Resin Monolithic Articles>

[0144] [Examples 1-5, Comparative Examples 1 and 2: The Effect of Aromatic Ring Ratio on Cured Epoxy Resins]

[0145] Using a doctor blade coater, the epoxy resin compositions of Reference Examples 1-7 were applied at a rate of 100 g / m². 2 The resin per unit area weight was coated onto release paper to produce an epoxy resin film. A reinforcing fiber sheet (with a unit area weight of 193 g / m²) formed by unidirectionally aligning carbon fiber 1 (coated with sizing agent compound 1) was then drawn out. 2 While moving it in one direction, the area weight of the thermoplastic resin (PPS) is 120 g / m². 2 A resin sheet is disposed on the reinforcing fiber sheet, and the thermoplastic resin is melted by heating with an IR heater and adhered to the entire surface of one side of the reinforcing fiber sheet. Then, pressure is applied by a clamping roller with a surface temperature maintained at 100°C lower than the melting point of the thermoplastic resin, so that PPS is impregnated in the reinforcing fiber sheet, and then cooled to obtain an intermediate. Next, the epoxy resin film is stacked on the opposite surface of the intermediate to the surface impregnated with thermoplastic resin, and the epoxy resin composition is impregnated in the intermediate while being heated and pressurized by a hot roller to obtain a prepreg blank [I].

[0146] Using a doctor blade coater, the epoxy resin compositions of Reference Examples 1-7 were applied at a rate of 50 g / m². 2 An epoxy resin film was fabricated by coating a unit area weight of resin onto release paper. This epoxy resin film was then laminated onto a reinforcing fiber sheet (unit area weight 193 g / m²) formed by unidirectionally spinning carbon fiber 1. 2 On both sides of the prepreg, the epoxy resin composition is impregnated into the reinforcing fiber while being heated and pressurized by hot rollers to obtain the prepreg blank [II].

[0147] The prepreg blanks [I] and [II] prepared as described above are cut into specified sizes to obtain 2 prepreg blanks [I] and 4 prepreg blanks [II]. A preform is fabricated by stacking a total of 6 prepreg blanks, with the outermost 2 blanks on each side as prepreg blanks [I], prepreg blanks [II] sandwiched in the middle, and all in the same reinforcing fiber direction. At this time, the preform is stacked with the outermost 2 blanks on each side as prepreg blanks [I], and the surface layer of both sides of the preform is a thermoplastic resin (PPS) layer. That is, 4 prepreg blanks [II] are sandwiched between 2 prepreg blanks [I], and the PPS-impregnated surface of the prepreg blanks [I] is the outermost side. The preform is placed in a compression molding die, and clamps and spacers are used as needed. While maintaining the shape, a pressure of 0.6 MPa is applied by a press, and the mixture is heated at 180°C for 120 minutes to obtain fiber-reinforced resin for evaluating compressive strength and observing cross-sections.

[0148] The prepreg blanks [I] and [II] prepared as described above are cut into specified sizes to obtain 2 prepreg blanks [I] and 6 prepreg blanks [II]. The axial direction of the reinforcing fiber is set to 0°, and the orthogonal direction of the axis is defined as 90°, with [0° / 90°] 2s (The symbol 's' indicates mirror symmetry) Preforms are fabricated by lamination. At this stage, the two outermost pieces on each side of the preform are stacked as prepreg blanks [I], and the surface layers on both sides of the preform are thermoplastic resin (PPS) layers. Specifically, six prepreg blanks [II] are sandwiched between two prepreg blanks [I], with the PPS-impregnated surface of the prepreg blanks [I] being the outermost layer. The preform is placed in a compression molding die, and clamps and spacers are used as needed. While maintaining the shape, a pressure of 0.6 MPa is applied using a press, and the mixture is heated at 180°C for 120 minutes, thereby obtaining fiber-reinforced resin for evaluating tensile shear bond strength.

[0149] Furthermore, with the 0° direction as the length direction of the test piece, the obtained fiber-reinforced resin for evaluating tensile shear bond strength was cut into two pieces with a width of 250 mm and a length of 92.5 mm, and dried in a vacuum oven for 24 hours. Then, the two pieces, each 250 mm wide and 92.5 mm long, were stacked with the 0° direction as the length direction and a width of 250 mm × length of 12.5 mm. A pressure of 3 MPa was applied at 300° and held for 2 minutes to fuse the overlapping surfaces, resulting in an integrally molded article for evaluating tensile shear bond strength.

[0150] The evaluation results of the physical properties of fiber-reinforced resin and integrally molded products are shown in Table 2.

[0151] [Table 2]

[0152]

[0153] [Examples 6-8: The effect of the thermal conductivity of the reinforcing fiber]

[0154] Using the epoxy resin composition of Reference Example 1, the type of carbon fiber constituting the reinforcing fiber sheet was changed as described in Table 3. Otherwise, the operation was the same as in Example 1 to obtain the fiber-reinforced resin and the integral molded article.

[0155] The evaluation results of the physical properties of the fiber-reinforced resin and the integrally molded article are shown in Table 3 together with the evaluation results of Example 1.

[0156] [Table 3]

[0157]

[0158] [Examples 9-12, Comparative Examples 3 and 4: The Influence of Thermoplastic Resin Type]

[0159] Using the epoxy resin compositions of Reference Examples 1, 6, and 7, the type of thermoplastic resin was changed as described in Table 4, and the welding temperature for obtaining the integrally molded article was also changed as described in Table 4. Otherwise, the procedure was the same as in Example 1 to obtain fiber-reinforced resin and integrally molded articles.

[0160] The evaluation results of the physical properties of the fiber-reinforced resin and the integrally molded article are shown in Table 4 together with the evaluation results of Example 1.

[0161] [Table 4]

[0162]

[0163] [Example 13: The effect of reinforcing fibers spanning the epoxy resin cured region and the thermoplastic resin region]

[0164] The fiber-reinforced resin of Example 13, which does not have reinforcing fibers crossing the boundary and contacting the two resin regions, was prepared by the following method. A prepreg blank [II] prepared using the epoxy resin composition of Reference Example 1 and by the same method as in Example 1 was cut into specified sizes and stacked in a total of 6 sheets so that all fibers were aligned in the same reinforcing fiber direction. Then, PPS with a unit area weight of 120 g / m² was attached to both surfaces. 2 The membrane was used to fabricate preforms. Then, following the same procedure as in Example 1, the resin was heated and pressurized using a press to obtain fiber-reinforced resin for evaluating compressive strength and observing cross-sections.

[0165] The prepreg blank [II] obtained above is cut into the specified size, the axial direction of the reinforcing fiber is set to 0°, and the orthogonal direction of the axis is defined as 90°, with [0° / 90°] 2s (The symbol 's' indicates mirror symmetry) After lamination, the weight per unit area of ​​PPS attached to both surfaces is 120 g / m². 2 The membrane was used to make a preform. Then, following the same procedure as in Example 1, the membrane was heated and pressurized using a press to obtain a fiber-reinforced resin for evaluating tensile shear bond strength. This resin was then fused together using the same method as in Example 1 to obtain an integrally molded product.

[0166] The evaluation results of the physical properties of the fiber-reinforced resin and the integrally molded article are shown together with the evaluation results of Example 1 in Table 5.

[0167] [Table 5]

[0168] [Table 5]

[0169]

[0170] [Examples 14-18: The Influence of Surface Free Energy on Reinforcing Fibers]

[0171] Using the epoxy resin composition of Reference Example 1, the type of carbon fiber constituting the reinforcing fiber sheet was changed as described in Table 6. Otherwise, the operation was the same as in Example 1 to obtain the fiber-reinforced resin and the integral molded article.

[0172] The evaluation results of the physical properties of the fiber-reinforced resin and the integrally molded article are shown together with the evaluation results of Example 1 in Table 6.

[0173] [Table 6]

[0174]

[0175] Explanation of reference numerals in the attached figures

[0176] 1: Reinforcing fibers

[0177] 2: Thermoplastic Resin Area

[0178] 3: Epoxy resin cured area

[0179] 4: Observe the image

[0180] 5: Boundary surface

[0181] 6: Baseline

[0182] 7: Vertical baseline

[0183] 8: Interface Curves

Claims

1. A fiber-reinforced resin comprising reinforcing fibers and having an epoxy resin cured region and a thermoplastic resin region formed on the surface of the epoxy resin cured region, wherein, The epoxy resin cured product is defined as having an aromatic ring content of 50% to 90% by mass in all molecules constituting the epoxy resin cured product. The epoxy resin cured product is a cured product of an epoxy resin composition in which the average epoxy equivalent of all epoxy resins is 180 g / eq or more and 255 g / eq or less. The thermal conductivity of the reinforcing fiber is above 3 W / (m·K) and below 100 W / (m·K). The surface free energy, determined by the Wilhelmi method, is 10 mJ / m. 2 Above 50mJ / m 2 The following reinforcing fibers are used as the reinforcing fibers. The reinforcing fiber exists that crosses the boundary between the thermoplastic resin region and the epoxy resin cured region and is in contact with both resin regions.

2. The fiber-reinforced resin as described in claim 1, wherein, The epoxy resin cured region and the thermoplastic resin region each form layers adjacent to each other.

3. The fiber-reinforced resin as described in claim 1 or 2, wherein, The thermal conductivity of the reinforcing fiber is above 3 W / (m·K) and below 50 W / (m·K).

4. The fiber-reinforced resin as described in claim 1 or 2, wherein, The epoxy resin cured product is a cured product of an epoxy resin composition comprising an epoxy resin having a polycyclic aromatic hydrocarbon backbone or a biphenyl backbone.

5. The fiber-reinforced resin as described in claim 1 or 2, wherein, The epoxy resin cured product is a cured product of an epoxy resin composition containing a polyamine compound with an average active hydrogen equivalent of 55 g / eq. to 100 g / eq.

6. The fiber-reinforced resin as described in claim 1 or 2, wherein, The epoxy resin cured product is a cured product of an epoxy resin composition that has a heat loss rate of less than 1.0% when the cured product obtained by heating at 180°C for 120 minutes is held at 300°C for 2 minutes, and has a glass transition temperature of more than 180°C and less than 350°C.

7. The fiber-reinforced resin as described in claim 1 or 2, wherein, The average roughness length RSm of the boundary surface between the epoxy resin cured region and the thermoplastic resin region is less than 100 μm, and the average roughness height Rc is more than 3.5 μm.

8. A one-piece molded article, which is formed by fusing the fiber-reinforced resin of any one of claims 1 to 7 with other components via the thermoplastic resin region.

Citation Information

Patent Citations

  • Process for producing carbon fiber

    JP2010255168A

  • Layered product, electromagnetic-shielding molded object, and processes for producing these

    WO2004060658A1

  • Epoxy resin composition, prepreg, and carbon fiber-reinforced composite material

    CN107922591A

  • Prepreg, laminate, and integrated molded article

    CN114761468A

  • Layered product, electromagnetic-shielding molded object, and processes for producing these

    EP1593491A1